Intake of cocoa products and risk of type-2 diabetes: the multiethnic cohort - Maskarinec, G.; Jacobs, S.; Shvetsov, Y.; Boushey, Carol; Setiawan, V.; Kolonel, L.; Haiman, C.; Le Marchand, L. (Nature Publishing Group, 2018)
© 2018 Macmillan Publishers Limited, part of Springer Nature Background/objectives: As cocoa products may be protective against chronic disease due to their polyphenol content, the current study determined the association of chocolate consumption and flavanol intake with type-2 diabetes (T2D) incidence in the Multiethnic Cohort (MEC) Study. Subjects/methods: The analysis included 151,691 participants of Native Hawaiian, Japanese American, Latino, African American, and white ancestry with 8487 incident T2D cases after 7.8 ± 3.5 years of follow-up. T2D status was based on three self-reports and confirmed by at least one of three administrative data sources. Dietary intake was assessed using a validated quantitative food frequency questionnaire, and flavanols from cocoa products were estimated from self-reported consumption of chocolate candy and drinks. Cox hazard regression, adjusted for potential confounders was applied to estimate hazard ratios (HR) and 95% confidence intervals (CI). Results: For chocolate candy, both the highest vs. lowest (=10 vs. < 1 g/day) consumption (HR = 0.90; 95% CI, 0.83–0.97; p trend = 0.01) and the frequency (=4/week vs. < 1/month) of intake (HR = 0.81; 95% CI, 0.72–0.91; p trend = 0.0002) were inversely associated with T2D. The estimated flavanol intake from cocoa products (=3 vs. < 1 mg/day) also showed an inverse association with T2D risk (HR = 0.93; 95% CI, 0.88–0.99; p trend = 0.02). Significant interaction terms indicated that the inverse relation was limited to Japanese Americans, normal-weight individuals, and to those without comorbidities. Conclusions: The current study confirms previous reports that participants with high intake of chocolate products and cocoa-derived flavanols experience a reduced risk of developing T2D even after controlling for sugar intake, diet quality, and other aspects of the diet.